2012
DOI: 10.1111/j.1365-2745.2012.01997.x
|View full text |Cite
|
Sign up to set email alerts
|

Species and organ specificity of fungal endophytes in herbaceous grassland plants

Abstract: Summary1. Foliar endophytic fungi in herbaceous plants are known to be diverse, yet studies characterizing the fungal communities in roots and shoots of plants across time are absent. These fungi are supposedly ubiquitous in nature, infecting plants through airborne spores. As many foliar endophytes can also exist in soil, we hypothesized that there would be a strong similarity between root and shoot endophytes in any given plant species and that differences between plant species would be greater than those be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
98
3
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 42 publications
20
98
3
2
Order By: Relevance
“…It is also noteworthy that, in the present study, roots host higher diversity and were more frequently colonized by fungal endophytes than aboveground organs. Similar result has been obtained from studies on other halophytic (Kannan et al 2014) and non-halophytic (Wearn et al 2012) plants. The aboveground plant organs are exposed to stress factors such as UV radiation, desiccation and lack of nutrients (Lindow and Brandl 2003) that could account for the lower fungal diversity and colonization of leaves and twigs comparatively to roots.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is also noteworthy that, in the present study, roots host higher diversity and were more frequently colonized by fungal endophytes than aboveground organs. Similar result has been obtained from studies on other halophytic (Kannan et al 2014) and non-halophytic (Wearn et al 2012) plants. The aboveground plant organs are exposed to stress factors such as UV radiation, desiccation and lack of nutrients (Lindow and Brandl 2003) that could account for the lower fungal diversity and colonization of leaves and twigs comparatively to roots.…”
Section: Discussionsupporting
confidence: 80%
“…(Fabaceae), and they found little similarity between these plant organs. Wearn et al (2012) also reported low similarity on endophytic fungal assemblages between roots and leaves of three cooccurring non-halophytes grassland forbs (Cirsium arvense, Plantago lanceolata and Rumex acetosa).…”
Section: Discussionmentioning
confidence: 99%
“…In most of these surveys of natural plant hosts, nemato-and entomopathogens occur at a low frequency in populations of particular host plant species (i.e., VĂĄzquez de Aldana et al 2013 ). However, exceptions to this occur, and a predominance of some species of these fungi has been reported in the endophytic mycobiota of some plant hosts (Miles et al 2012 ;Wearn et al 2012 ). Some entomopathogenic taxa have been identifi ed as natural endophytes in more than one host plant species (i.e., B. bassiana , Lecanicillium lecanii ) ( Growth promotion activities and their indirect effect on lower susceptibility to pest and diseases are represented in green , while direct protection against pest, pathogens, and nematodes are represented in red in general terms, a relatively common endophyte.…”
Section: Presence Of Entomopathogenic and Nematophagous Fungal Endophmentioning
confidence: 98%
“…Therefore, considering the abundance of grasses on earth, and the apparently ubiquitous relationships of these fungi with grasses, these endophyte taxa can be considered important organisms in grass dominated ecosystems. Furthermore, some of these fungal genera have also been reported as dominant endophytes in leaves of dicotyledonous plant species, like Arabidopsis thaliana (GarcĂ­a et al 2012), Vitis vinifera (GonzĂĄlez and Tello 2011), Cirsum arvense, Plantago lanceolata, Rumex acetosa (Wearn et al 2012), and others.…”
Section: Periconiamentioning
confidence: 99%